The Impact of Covid-19 on Zakat Shares Potential in Indonesia - Nono Hartono; Helen Prisila; Gustani . (International Journal of Zakat, 2021)
This study aims to analyze the impact of Covid-19 on the potential for zakat on shares. The method used is a quantitative method. The sample used is a company registered with the Jakarta Islamic Index (JII), as many as 23 companies, the determination of the sample is determined by judgment sampling technique. The data analysis method used is descriptive method. The method of calculating the potential zakat of shares is calculated by multiplying the number of shares and the average share price then multiplying the nishab of zakat on shares. Then the t-test is carried out to prove whether there is a difference in the potential for zakat on shares before and during Covid-19. The potential for zakat on shares in 2020 is Rp. 39.8 trillion and lower than in 2019. The t-test results show that there is a significant difference between zakat potential in 2019 and the Covid-19 pandemic in 2020. This illustrates that the potential for zakat on shares in JII has been negatively affected by the Covid pandemic. -19 as the company's share price decreases. The potential for zakat shares in the infrastructure, utilities and transportation sectors is most affected by the Covid-19 pandemic compared to other sectors. The existence of a large-scale social restriction policy has an effect on the movement of people in using transportation, which causes a decrease in the stock price of the transportation sector